Stability in a network economy : the role of institutions - Robert Paul Gilles; Emiliya A. Lazarova; Pieter H. M. Ruys (Stability in a network economy : the role of institutions, 2015)
We consider an economy in which agents are embedded in a network of potential value-generating relationships. Agents are assumed to be able to participate in three types of economic interactions: Autarkic self-provision; bilateral interaction; and multilateral collaboration. We introduce two stability concepts and provide sufficient and neccessary conditions on the networks structure that guarantee existence, both in the absence of externalities from cooperation as well as under crowding conditions. We show that institutions such as socioeconomic roles and hierachical leadership structures are neccessary for stability. In particular, the stability of more complex economic outcomes requires more stringent restrictions on the underlying network which imply more complex institutional rules that govern economic interactions. Thus, we provide support for the theory of co-evolution of institutions and economic outcomes.
10.2139/ssrn.2506643; 10.2139/ssrn.2506643; 2813346-8; 819416452